FOOTSTEPS POWER GENERATION USING PIEZOELECTRIC ENERGY HARVESTER - Muhammad Haroon; Aitazaz Ahmed (Spectrum of Engineering Sciences, 2025)
Pakistan faces a persistent energy crisis, with frequent power outages and reliance on costly, environmentally harmful fossil fuels, necessitating sustainable energy solutions. This study explores piezoelectric energy harvesting through footstep power generation using Lead Zirconium Titanate (PZT) transducers to address localized energy demands in urban settings. The system converts mechanical stress from pedestrian and vehicular traffic into electrical energy, suitable for low-power applications like LED lighting and mobile charging stations. Implemented in high-traffic areas such as crosswalks, universities, and railway stations, the prototype employs 40 PZT transducers arranged in parallel, supported by a wooden frame with springs for durability. Simulations using COMSOL Multiphysics predicted a voltage output of -58V under a 10N load, while experimental results yielded 20V and 2.3 mW from a 16-sensor array, sufficient for small-scale applications. Future improvements include advanced materials, resonant frequency optimization, and hybrid integration with solar or wind energy to enhance efficiency and applicability, particularly in Pakistan’s congested urban centers, contributing to decentralized, eco-friendly energy solutions.